The Effect of Barrel Configurations on the Porosity During HVAF Thermal Spray Ni-Based Amorphous Coatings: Numerical Simulation and Experiment - Nianchu Wu; Tingting Li; Xiaotian Su (Archives of Metallurgy and Materials)
The relationship between barrel configurations and porosity of a Ni-based amorphous coating (AM) that is fabricated using a high-velocity air fuel (HVAF) process was revealed by both numerical and experimental methods. A computational fluid dynamics model was applied to investigate the gas-flow field and the behavior of in-flight particles with various barrel configurations. It is found that barrel length obviously affects the particle velocity and temperature while it has a slight influence on the particle velocity and temperature. The longer the barrel length (diameter), the higher the flame (particle) velocity and temperature. By analyzing both particle velocity and temperature, the optimal barrel configuration (4E) to achieve low-porosity coatings was predicted. These calculations were experimentally verified by the production of a low-porosity (2.09%) Ni-based AM that was fabricated by HVAF using the predicted optimal barrel configuration.